VISUAL AND AESTHETIC CONSISTENCY IN TRANSMEDIA ADAPTATIONS: A COMPARATIVE ANALYSIS IN GRIMM BROTHER’S AND DISNEY - Divya, A. J; Raa, M. Richard Robert (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research delves into the multifaceted Visual and aesthetic consistency in Transmedia adaptations: a comparative analysis in Grimm brother’s and Disney. This study aims to unravel the diverse layers of moral messages embedded in these timeless tales, shedding light on how they influence and shape the moral compass of young readers. Drawing on classic works such as "Grimm's Fairy Tales" by the Grimm Brothers and Disney adaptations like "Cinderella" and "Snow White," the research navigates through the distinct narrative approaches employed by each tradition. It scrutinizes the moral landscapes presented in these stories, examining the characters, plot developments, and underlying themes that contribute to the moral fabric of each narrative. By dissecting the tales, the study seeks to identify potential variations and evolutions moral perspectives between the original Grimm versions and the adapted Disney renditions. The analysis not only explores overt moral lessons but also delves into subtle nuances, exploring the cultural and societal contexts that may have influenced the moral choices made in these narratives. Furthermore, the research addresses the implications of these moral layers on the development of ethical understanding in children. It considers the potential impact of contrasting moral frameworks presented in Grimm and Disney stories, raising questions about the role of literature in shaping young minds and instilling values. In conclusion, "Fairy tales Unmasked" offers a nuanced exploration of the intricate moral tapestry woven into children's literature, unravelling the distinct moral landscapes in Grimm vs Disney stories.